2019
DOI: 10.3389/fmicb.2019.02892
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transmission in the One Health Microbiosphere and the Channels of Antimicrobial Resistance

Abstract: Antibiotic resistance is a field in which the concept of One Health can best be illustrated. One Health is based on the definition of communication spaces among diverse environments. Antibiotic resistance is encoded by genes, however, these genes are propagated in mobile genetic elements (MGEs), circulating among bacterial species and clones that are integrated into the multiple microbiotas of humans, animals, food, sewage, soil, and water environments, the One Health microbiosphere. The dynamics and evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 143 publications
0
75
0
Order By: Relevance
“…Although not belonging to the antibiotic resistome, genes frequently associated with resistance to other antimicrobials, such as heavy metals or biocides, as well as the genes of the MGEs backbones, eventually involved in the transmission and selection of ARGs among microbial populations, the mobilome at large, are also relevant to track the emergence and dissemination of AR among different habitats ( Lanza et al, 2015 ; Martinez et al, 2017 ; Baquero et al, 2019 ).…”
Section: Defining the Bricks Building Up Antibiotic Resistance In A Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not belonging to the antibiotic resistome, genes frequently associated with resistance to other antimicrobials, such as heavy metals or biocides, as well as the genes of the MGEs backbones, eventually involved in the transmission and selection of ARGs among microbial populations, the mobilome at large, are also relevant to track the emergence and dissemination of AR among different habitats ( Lanza et al, 2015 ; Martinez et al, 2017 ; Baquero et al, 2019 ).…”
Section: Defining the Bricks Building Up Antibiotic Resistance In A Gmentioning
confidence: 99%
“…HGT processes are recognized as the main mechanisms for transmission of genetic information ( Baquero, 2017 ). From the ecological point of view, HGT should be understood as a cooperative mechanism that allows the exploitation of common goods as ARGs ( Baquero et al, 2019 ) by different members within bacterial communities. In fact, some studies suggest that the ecological consequences of HGT events in AR evolution are contingent on the cooperation of complex bacterial communities, besides the acquisition of individual adaptive traits ( Smillie et al, 2011 ).…”
Section: Defining the Bricks Building Up Antibiotic Resistance In A Gmentioning
confidence: 99%
“…The possibility of HGT occurrence increases due to the proximal contact of donorrecipient genomes with each other (Adato et al, 2015;Brown and Wernegreen, 2019). The results of phylogenetic and eukaryotic nuclear genome analysis showed that the information expressed by HGT can affect a wide variety of genes (Baquero et al, 2019;Campos et al, 2019;Leclerc et al, 2019). Accordingly, HGT is essential for the evolution of both prokaryotic and eukaryotic genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Sharedness with Lactococcus and Lactobacillus was found to be below 1%. This analysis can be certainly biased by the number of genomes of each species available in databases, but in general pangenome gene connectivity should reflect the possibility of sharing antibiotic resistance genes (Baquero, Coque, Martínez, Aracil‐Gisbert, & Lanza, ).…”
Section: Introductionmentioning
confidence: 99%